Phylogeography of Invasive Rats in New Zealand - Russell, James C.; Robins, Judith H.; Fewster, Rachel M. (Frontiers in Ecology and Evolution, 2019)
Two species of invasive rats (Rattus norvegicus and R. rattus) arrived in New Zealand with Europeans in the mid to late 18th and 19th century respectively. They rapidly spread across the main islands of New Zealand and its offshore islands, displacing the historically introduced R. exulans. Today both species are widespread although the distribution of the sub-dominant R. norvegicus is patchy. Tissue samples were obtained from 425 R. rattus and 130 R. norvegicus across the New Zealand archipelago and neighbouring islands. We sequenced a standard 545 base pair section of the mitochondrial D-loop in order to construct a modern phylogeography of the two species and to make inference on historical invasion pathways and spread across the country. We found limited diversity in R. norvegicus haplotypes, with two widespread haplotypes across New Zealand and its offshore islands most likely corresponding to two independent invasions, potentially with English and Chinese origins. In contrast we found widespread diversity in R. rattus haplotypes across New Zealand and its offshore islands, most likely corresponding to at least four independent invasions to the main North and South Islands, Great Barrier Island archipelago, and Stewart Island archipelago. The most common R. rattus haplogroup was found throughout New Zealand and many of its offshore islands, as well as neighbouring islands in the Tasman Sea, and has been documented elsewhere across the Pacific, but with European origins. We also found both geographic partitioning and secondary invasions of haplotypes within the main North and South Island. In addition to distinct haplogroups differing by over three base pairs, which exhibit geographical partitioning suggestive of independent invasion events, for both species we also found instances of single base-pair differences within localities, elevating haplotype diversity. The geographical distribution of pelage colour morphs also correlates with haplotype distribution, lending further support to the hypothesis and role of independent invasion events.